High dairy products intake modifies the correlation between α-tocopherol levels and serum proteins related to lipid metabolism in subjects at risk of type 2 diabetes - Mahdavi, Atena; Leclercq, Mickael; Bodein, Antoine; Gotti, Clarisse; Greffard, Karine; Bilodeau, Jean-François; Droit, Arnaud; Lebel, Michel; Rudkowska, Iwona (Journal of functional foods, 2023)
[Display omitted] •Increasing dietary fat intake could improve α-tocopherol bioavailability.•Proteomics offer a useful approach for identifying protein biomarkers.•Serum α-tocopherol associates with serum proteins that regulate lipid homeostasis.•High dairy intake modifies the correlations between α-tocopherol and proteomics. Increasing dairy fat intake is expected to improve α-tocopherol bioavailability and could be beneficial for improving T2D risk factors. The aim of this study is to investigate the relationship between α-tocopherol levels and serum protein profiles before and after intake of adequate dairy (AD) or high dairy (HD) products in hyperinsulinemia patients. In this crossover study, dietary intake of 25 subjects with hyperinsulinemia (54 ± 14 yrs and BMI 31 ± 3) included: 1- pre-AD intake; 2- pre-HD intake; 3- post- AD intake (≤2 servings/day); and 4- post-HD intake (≥4 servings/day) assessed by food frequency questionnaire. In pre-AD, post-AD and pre-HD, α-tocopherol positively correlated with proteins mainly involved in lipid metabolism (rho > 0.40; P < 0.05). In contrast, α-tocopherol did not correlate with these biological processes in post-HD. Thus, these findings indicate that α-tocopherol levels are associated with serum proteins that regulate lipid homeostasis. However, the increase intake of dairy products modified these associations in hyperinsulinemia subjects.